PENGARUH PUPUK BIOFILMED FERTILIZER TERHADAP HASIL BAWANG MERAH PADA TANAH ALFISOL JUMANTONO - Wiratama, Ristiya Adi; Iswari, Aryani Tri; Sumarno; Sudadi; Widijanto, Hery (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2025)
Shallot requires sulfur nutrient to improve color, flavor and reduce shrinkage during it storages as well as to enlarge the shallot bulbs. Alfisols had low available sulfur so biofilmed fertilizer application was expected to increase S-uptake nutrient and yield of shallot production. This research was conducted at the Research Center and Development of Dryland of Sebelas Maret University Surakarta in Jumantono, Karanganyar in June 2014 to March 2015 to study the effect of formula and dosage of biofilmed fertilizer on S-uptake and yield of shallot. The experiment was arranged in factorial completely randomized design (CRD) with two factors, namely three formulas and four dosages of biofilmed fertilizer. The variables observed were available S, S-uptake, growth and yield of shallot. Data was analyzed by F test followed by DMRT at 95% of level confident. The results showed that biofilmed fertilizer formula and dosage affected significantly on S-available and S-uptake at harvest. Biofilmed fertilizer with F1 (consortium of sulfur oxidizing bacteria, solvent fungi K, solvent bacteria P, and fastening bacteria N2) and D2 was 100% equivalent to dosage recommendation of NPK and gave the highest of shallot yield 54,634g or equivalent to 14.53 tons/ ha.